Analisis Pelaksanaan Program Selamatkan Rawa Sejahterakan Petani (SERASI) di Kabupaten Banyuasin - Sutinah, Sutinah; Azhar, Muhammad Fakhri (@-Publik: Jurnal Administrasi Publik, 2022)
Gaining a deep understanding of the implementation of the Save Rawa Prosperous Farmers program in Banyuasin Regency was the goal of this study using a qualitative method by interviewing informants. The results showed that the Save Rawa Welfare for Farmers program in Banyuasin Regency had been implemented but could not be said to be optimal because there were still several obstacles. From the planning dimension, there is still a lack of budget or funds to implement the SERASI program, and currently there are only 2 available extension workers or assistants, considering the number of existing farmer groups. The required support staff is 3-5 employees. Another obstacle is the number of excavators available in the field is still small. Based on the organizational dimensions, the division of labor is carried out in accordance with the established organizational structure. Coordination is also carried out by involving related parties in the implementation of the SERASI program. Based on the dimensions of mobilization, there are still few farmers or members of farmer groups who understand physical work (construction) and management. For example building a sophisticated network, building a gateway and deploying heavy equipment. Another obstacle is that there are too many administrative requirements for farmer groups to apply for the SERASI program. Based on the supervision dimension, supervision of the implementation of the SERASI program is carried out through direct supervision or meetings. In addition, the SERASI Program Implementation Results Report is also prepared by the Department of Agriculture, Food and Horticulture as well as farmer groups and communicated regularly and in a timely manner.